Guilt a contemporary introduction - Carveth, Donald L. 1944- (Routledge, 2024)
This insightful and innovative book sheds light on the complexity of the concept of guilt, while exploring aspects of guilt that have previously been overlooked in psychoanalytic theory and discourse